For Jimmy, Wes and Oliver [compact disc] - McBride, Christian; DeFrancesco, Joey; Whitfield, Mark (Mack Avenue Records, 2020)
Christian McBride solidifies his role as the champion of the past, present, and future of jazz with his Grammy Award-winning Big Band's new album in tribute to Jimmy Smith, Wes Montgomery, and Oliver Nelson. Featuring special guests Joey DeFrancesco and Mark Whitfield, this album honors the historical legacy of the jazz legends who shaped the soul of music for generations to come.